THE IMPORTANCE OF DIGITAL RESOURCES IN ORGANIZING INDEPENDENT WORK OF MEDICAL STUDENTS - Melibayeva Faragat Madaminovna (Modern American Journals, 2025)
This scientific article comprehensively examines the role of digital resources in effectively organizing independent learning activities in the field of medical education and their positive impact on the learning process. In the 21st century, medical education has entered a new phase in close integration with digital technologies, which has become a key factor in developing students’ clinical reasoning, analytical thinking, evidence-based decision-making, and professional competencies. The article analyzes the fundamental principles of organizing independent work using digital resources in higher medical institutions, explores the available opportunities, identifies existing challenges, and discusses mechanisms for overcoming them.
Keywords: Medical education, digital resources, independent learning, electronic library, distance learning, virtual simulation, medical platforms, information technology, digital pedagogy, artificial intelligence.